Analysis of HEM applicability for a subcritical flashing ejector at low motive pressure - Gonçalves, Karla; Varga, Szabolcs; Butrymowicz, Dariusz; Śmierciew, Kamil (Frontiers in Mechanical Engineering, 2024)
Validated CO2 ejector models are essential for developing high-performance refrigeration and heat pump cycles. This study focuses on assessing the Homogeneous Equilibrium Model’s applicability to simulate a CO2 flashing ejector at a reduced pressure of 0.47. The model was implemented in FLUENT, integrating a user-defined real gas model. Simulation results with different boundary condition options were compared to experimental data. The analysis was carried out to evaluate the predictive capabilities of the model and assess the experimental data quality. The results indicate that the developed model accurately estimated the motive mass flow rate, with a maximum relative error of 5.7%, showing better performance than previously reported data. The entrained flow rate, assuming double choking operation, was significantly higher than the experimental measurement, and the CFD-predicted wall static pressure underestimated the experimental profile, suggesting single-choked ejector operation. In contrast, the outflow density was better predicted under the same assumption, with an average error of 8.6%. Nevertheless, the simulated temperature profiles showed good agreement with the experimental data, especially when using the experimental entrained mass flow rate as a boundary condition.